Configure the Symmetrical and Asymmetrical Paths of Brand Equity and Relationship of Firm Created Content and User Generated Content as Antecedent - Aditya Halim Perdana Kusuma Putra; Nurani; Gunawan Bata Ilyas; Yulia Tri Samiha; Setyani Dwi Lestari (Jurnal Manajemen Bisnis, 2021)
This study aims to investigate in the relationship FCC, UGC, Customer Experience satisfaction towards Brand Equity and Purchase Decision on the subject of e-commerce research in Indonesia (e.g., Lazada, Tokopedia, and Bli-Bli). This study used two research methods: exploratory research (exploratory research) and descriptive research (descriptive analysis). This study's total population was 200 eligible. The collection data with online survey. This study's testing phase is through three phases: first, the reliability of the construct configuration for brand association, brand awareness, brand reputation, and brand performance on brand equity. Second, the relationship that explains the direct and indirect effects of UGC and FCC on brand equity and purchase intention; third, the relationship that demonstrates the impact of variable customer experience satisfaction on brand equity and purchase intention. The result of this study shown from the seven symmetrical paths, the direct relationship is found significant results except for variable relationships such as UGC and FCC on Purchase Intention, which states that there is no significant effect. For example, the indirect relationship between FCC and Purchase Intention mediated by the Brand Equity variable states that there is no positive and significant effect. Except for the relationship between UGC on Purchase Intention mediated by Brand Equity and Brand Equity on Purchase Intention mediated by the Customer Experience Satisfaction variable. Both found that there was a positive and significant relationship.